Desain dan Analisis Mata Pisau Pencacah Untuk Pengolahan Sampah Plastik Menggunakan Finite Element Analysis - Haryo Pranoto, Sigiet; Yatnikasari, Santi; Noor Asnan, Muhammad; Ilmal Yaqin, Rizqi (P3M Politeknik Negeri Cilacap, 2020)
Plastic waste is one of the environmental problems in Indonesia. Plastic waste is a type of waste that is difficult to decompose, so it needs special handling for processing the problem. One alternative offered is by making a plastic chopper machine. One of the manufacturing of a machine is to design and analyze the components used. The blade is one of the important components of a plastic chopper. Model simulation of the blade itself needs to be done to analyze the performance of the blade during the performance of the machine. Simulation modeling is done using CAE software.. The form of meshing in the blade model is using tetrahedral and the meshing ratio is close to 1. The results obtained from the blade modeling process are the maximum Von mises stress on the loading of 300N, 500N, and 700N respectively at 6.752 x 10-3 MPa, 2.845 x 10- 3 MPa and 1,575 x 10-3MPa. While the amount of displacement in the variation of loading 300N, 500N, and 700N respectively has a value of 6.752 x 10-2 mm, 1.125 x 10-1 mm and 1.575 x 10-1 mm. The safety factor in this simulation is produced which has a value of 15, which means it is safe for all loading variations because it has a value of more than 1.